Keputusan Memilih Jasa Wedding Organizer Berdasarkan Physical Evidence Factor (Studi Kasus pada CV. Anpian Wedding Organizer Ciamis) - Hadiani, Dian; Munawar, Andri Helmi; Supriatna, Nana (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
The decision process to choose the services of a wedding organizer is already considered an identity and a prestige now. With the number of start-ups engaged in this field that only rely on capital "brave" but does not have its own outlet space. Research evidence based on physical evidence on the CV. Anpian Wedding Organizer Ciamis. The assessment used is quantitative with an explanatory method. The technique of determining the sample using puposive sampling, with a total sample of 58 respondents. Data collection using questionnaires and interviews. The data is processed using validity and reliability test, coefficient of agreement and determination, multiple regression analysis, significance test. the influence of physical evidence on the decision to choose services by 57%. The results of the analysis: physical evidence elements servicescape dimensions and other physical communication partially or simultaneously have a positive and significant influence on the decision to choose wedding organizer services